EARLY CHILDHOOD PRE-SERVICE TEACHERS’ AWARENESS AND PERCEPTION OF THE 2030 AGENDA FOR SUSTAINABLE DEVELOPMENT GOALS (Unilorin Journal of Lifelong Education, 2023)
This study examined early childhood pre-service teachers’ perception and awareness of the 2030 agenda for Sustainable Development Goals: Implications for 21st-century classroom teaching effectiveness in universities in Lagos State. The study adopted the descriptive survey research design. The research population comprised all 586 pre-service student teachers of early childhood education at the University of Lagos and Lagos State University. The study sample was 130 (one hundred and thirty) students selected using a simple random sampling technique. It utilized the researchers-designed Sustainable Development Goals and Early Childhood Education Questionnaire (SDGSECHEQ) was used to collect relevant data virtually after its conversion to a Google Form questionnaire. The reliability test yielded a reliability coefficient of 0.89. The whole data collection lasted six (6) weeks. The collected data were analysed utilizing frequency count, percentage, and mean. Findings from the study showed that the level of early childhood undergraduates’ awareness of the 17 Sustainable Development Goals is high. In addition, they had a positive perception of Sustainable Development Goals. Based on these results, one of the core recommendations advanced was that early childhood education lecturers should ensure that the pre-service teachers attend conferences and workshops related to SDGs so that they can increase their knowledge as regards the SDGs. Again, the Universities in Lagos State should strive to increase their capacity and make available expert personnel in the areas of early childhood education and SDG to ensure adequate sensitization of early childhood education on SDG issues.